Solar-Enhanced Plasma-Catalytic Oxidation of Toluene over a Bifunctional Graphene Fin Foam Decorated with Nanofin-like MnO(2) - Bo, Zheng (ACS Catal, 2020)
[Image: see text] In this work, we propose a hybrid and unique process combining solar irradiation and post-plasma catalysis (PPC) for the effective oxidation of toluene over a highly active and stable MnO(2)/GFF (bifunctional graphene fin foam) catalyst. The bifunctional GFF, serving as both the catalyst support and light absorber, is decorated with MnO(2) nanofins, forming a hierarchical fin-on-fin structure. The results show that the MnO(2)/GFF catalyst can effectively capture and convert renewable solar energy into heat (absorption of >95%), leading to a temperature rise (55.6 °C) of the catalyst bed under solar irradiation (1 sun, light intensity 1000 W m(–2)). The catalyst weight (9.8 mg) used in this work was significantly lower (10–100 times lower) than that used in previous studies (usually 100–1000 mg). Introducing solar energy into the typical PPC process via solar thermal conversion significantly enhances the conversion of toluene and CO(2) selectivity by 36–63%, reaching ∼93% for toluene conversion and ∼83% for CO(2) selectivity at a specific input energy of ∼350 J L(–1), thus remarkably reducing the energy consumption of the plasma-catalytic gas cleaning process. The energy efficiency for toluene conversion in the solar-enhanced post-plasma catalytic (SEPPC) process reaches up to 12.7 g kWh(–1), ∼57% higher than that using the PPC process without solar irradiation (8.1 g kWh(–1)), whereas the energy consumption of the SEPPC process is reduced by 35–52%. Moreover, the MnO(2)/GFF catalyst exhibits an excellent self-cleaning capability induced by solar irradiation, demonstrating a superior long-term catalytic stability of 72 h at 1 sun, significantly better than that reported in previous works. The prominent synergistic effect of solar irradiation and PPC with a synergistic capacity of ∼42% can be mainly attributed to the solar-induced thermal effect on the catalyst bed, boosting ozone decomposition (an almost triple enhancement from ∼0.18 g(O(3)) g(–1) h(–1) for PPC to ∼0.52 g(O(3)) g(–1) h(–1) for SEPPC) to generate more oxidative species (e.g., O radicals) and enhancing the catalytic oxidation on the catalyst surfaces, as well as the self-cleaning capacity of the catalyst at elevated temperatures driven by solar irradiation. This work opens a rational route to use abundant, renewable solar power to achieve high-performance and energy-efficient removal of volatile organic compounds.